(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Today, the deterioration of the existing ecology and its prevention has become an urgent problem. This article examines the parametric changes that occur during the operation of vehicles and analyzes the resulting increase in emissions from the norm.